TINJAUAN LITERATUR : IMPLEMENTASI JAMINAN SOSIAL TERHADAP BANTUAN SOSIAL PADA MASA COVID-19 - Putri Lutfi Oktavia; Mas Esterilita; Hastin Trustisari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The social assistance program provided by the government through the National Social Security System (SJSN) has become increasingly important in helping those affected by the crisis and ensuring their basic rights are respected. This is in line with the conditions of the COVID-19 pandemic since 2020, which has placed significant pressure on the socio-economic conditions of many countries, including Indonesia. The aim of this paper is to review and analyze various studies on how the implementation of social security related to social assistance by the government during the COVID-19 pandemic has been carried out effectively or not. The method used in this paper is a narrative literature review, where the author conducted an online search using data collection techniques through literature review sourced from Google Scholar. Out of 20 literatures found, 4 were relevant to the keywords and met the criteria. The conclusion of this paper indicates that overall, the implementation of social assistance during the COVID-19 pandemic still needs to be improved and strengthened, especially in terms of data management, monitoring, and coordination among stakeholders to ensure that assistance can be distributed more effectively and efficiently to the target groups. In the future, the country must be prepared for the possibility of another pandemic. Therefore, the government needs to build a better and stronger system to implement social assistance policies.